English Teachers’ Perspectives: Peer-Assessment In 2013 Curriculum - Nova, Muhamad; Pratidina, Sonia Destrie; Syarif, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The implementation of 2013 curriculum results in a number of consequences in teachers’ negative conceptions of the peer-assessment implementation in the classroom. This current study aimed at revealing English teachers’ perspectives of peer-assessment as an assessment method in assessing students’ affective aspects. A survey research was conducted in the study which deployed questionnaires with 30 statements. 30 English teachers who applied 2013 Curriculum in their teaching and learning process participated in this study and the results exposed that most of these English teachers perceive positively the implementation of peer-assessment regarding its relation with character education and students’ attitude towards peer assessment. However, the application of peer-assessment for assessing students’ affective aspect still needs to be improved since the fairness of peer-assessment application is still questionable by the teachers. Therefore, further development of peer-assessment is required in order to promote its positive aspects.